Stroke recovery and rehabilitation - Stein, Joel, 1961- (Demos Medical, 2009)
Stroke Recovery and Rehabilitation is the new gold standard comprehensive guide to the management of stroke patients. Beginning with detailed information on risk factors, epidemiology, prevention, and neurophysiology, the book details the acute and long-term treatment of all stroke-related impairments and complications. Additional sections discuss psychological issues, outcomes, community reintegration, and new research.